Surface energy and mass balance at Purogangri ice cap, central Tibetan Plateau, 2001–2011 - Huintjes, Eva; Neckel, Niklas; Hochschild, Volker; Schneider, Christoph (Humboldt-Universität zu Berlin, 2015)
Most glaciers on the Tibetan Plateau are difficult to assess as they are located in remote regions at high altitude. This study focuses on the surface energy-balance (SEB) and mass-balance (MB) characteristics of Purogangri ice cap (PIC). A ‘COupled Snowpack and Ice surface energy and MAss balance model’ (COSIMA) is applied without observational data from the ground. The model is forced by a meteorological dataset from the High Asia Refined analysis. Model results for annual surface elevation changes and MB agree well with the results of a previous remote-sensing estimate. Low surface velocities of 0.026 0.012 m d–1 were measured by repeat-pass InSAR. This finding supports the validation of the steady-state COSIMA against satellite-derived surface changes. Overall MB of PIC for the period 2001–11 is nearly balanced (–44 kg m–2 a–1). Analysis of the model-derived SEB/MB components reveals that a significant amount of snowfall in spring is responsible for high surface albedo throughout the year. Thus, the average surface energy loss through net longwave radiation is larger than the energy gain through net shortwave radiation. The dry continental climate favours mass loss through sublimation, which accounts for 66% of the total mass loss.